Colunismo social e consagração de elites - Cruz, Karina Garcia Santos (2015)
This research aims to analyze how the social columnism serving elites of consecration instrument. It starts from the principle that social columnism is legitimate tool of social groups occupying strategic positions in society. Including the craft originates from positions of ratification demand of "great families" US traditional who lost power and prestige space for the new rich who emerged from the post Civil War. It is noted from the office of the emergence direct linkage between these two groups, the columnism establishing itself as one more tool in the consecration strategies of individuals concentrated in the social centers of power. To cope with the problem, the research was subdivided into three stages. The first aimed to highlight the consecration modes anchoring to the paths taken by certain individuals and groups, the strategies adopted (political coordination, the associations of power groups, political militancy, complimentary sessions congregation ceremonies, etc.) and social resources acquired during the socialization paths in different social spheres (family, school, college, professional, etc.), and bring to light the socio-historical and geographical circumstances that made it possible for such individuals and groups came to power spheres. The second phase aims to present social demands and socio-historical conditions that allowed the emergence of the craft of social columnist. It also exposes how the craft was noted as lucrative source for media companies, allowing the consolidation of the positions of gossip columnists and expanding their spaces in the newspapers. Besides showing attempts to establish the office of borders, demands by definition, for organization and control, to be seen as subarea of the journalism profession, rather interpreted craft and minimally recognized. The third set out to elucidate how the gossip columnists who make up the craft in Sergipe launch strategies, develop skills and accumulate social resources aimed at social consecration. So are explained the composition and characteristics of Sergipe gossip columnists are presented the routine work, the skills developed, the codes shared by working in the office, also they consume, how they build their numbered schedules, among other aspects. The main objective is to carry out the survey of biographical information (social origin, parents´ occupations, educational background, college and professional careers, travel, inserts in different spheres, marriage, tastes and lifestyles, etc.) in order to reveal how accumulate resources, launch strategies, develop skills for both self-consecration as the consecration of individuals and groups leaders. This part also contains an account of the observations noted in the field of daily counting to extract information to provide complete responses to the survey. The empirical universe considered consists of 6 active social columnists in newspapers Sergipe Mail, Journal of the City and Cinform. The research allowed to show that the columnists consecrated by developing certain skills, such interactional, creating strategies such as the marketing staff, mobilizing action repertoires, the lexicon adjective due to the creation of "good pictures", becoming important piece of gears and power structures.